The Effects of Insufflation Conditions on Rat Mesothelium - Andrew K. Davey; Jessica Hayward; Jean K. Marshall; Anthony E. Woods (Hindawi Limited, 2013)
Aim. The aim of this investigation was to examine the alterations in the peritoneum after cold dry CO2, heated dry CO2, and humidified heated CO2 at pressures equivalent to intraperitoneal pressures used in human laparoscopy. Methods. Eighteen rats were divided into 4 treatment groups-group 1: untreated control; group 2: insufflation with cold dry CO2; group 3: insufflation with heated, dry CO2; group 4: insufflation with heated and humidified CO2. The abdomen was insufflated to 5 mm/Hg (flow rate 50 mL/min) for 2 h. Twelve hours later, tissue samples were collected for analysis by light microscopy (LM) and scanning electron microscopy (SEM). Results. Group 1: no abnormalities were detected. Group 2: specimens revealed an inflammatory response with loss of mesothelium and mesothelial cell nuclei showing lytic change. Cells were rounded with some areas of cell flattening and separation. Group 3: some animals showed little or no alteration, while others had a mild inflammatory response. Mesothelial cells were rounded and showed crenation on the exposed surface. Group 4: specimens showed little change from the control group. Conclusions. The LM results indicate that insufflations with heated, humidified CO2 are the least likely to induce mesothelial damage.